Green Islamic education: integrating eco-theological values into Islamic curriculum to address the global environmental crisis - Iin Indra Nuraeni; Elis Ela Susila; Neni Utami Adiningsih; Sunsun Pradana Yogaswara; Lina Tio (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The accelerating global environmental crisis, marked by climate change, biodiversity loss, and resource depletion, demands innovative educational approaches that foster ecological awareness and responsible behavior. Within the Muslim context, Islamic education offers a unique ethical framework rooted in eco-theological values such as khalifah (stewardship), amanah (trust), mizan (balance), and maslahah (public benefit), which can be strategically aligned with the principles of Education for Sustainable Development (ESD). This study seeks to explore how Green Islamic Education can integrate these eco-theological values into Islamic curricula as a transformative response to global ecological challenges. Employing a descriptive qualitative design, the research draws on document analysis, semi-structured interviews with educators and religious leaders, and field observations in Islamic schools and pesantren implementing green initiatives. The results reveal that Islamic educational institutions hold significant potential to embed sustainability values through curriculum reform, eco-pesantren practices, and green madrasa programs supported by digital pedagogy and community engagement. Empirical evidence demonstrates that environmental ethics, when framed as part of religious obligation, enhance students’ ecological awareness, encourage sustainable lifestyles, and strengthen the linkage between faith and global responsibility.